The Kinshasa-based Kin ArtStudio in the Democratic Republic of Congo: visual arts spaces and the potential to challenge global art's representative and legitimizing mechanisms - Tshilumba Mukendi, Jean-Sylvain (Rhodes University, Faculty of Humanities, Department of Fine Art, 2019)
The emergence of visual art spaces over the past few decades on the African continent invites art practitioners, historians and critics to re-examine the conditions of production, diffusion and reception of contemporary art of Africa. In this thesis I critically engage with these conditions in relation to artworks and practices of the Democratic Republic of Congo, considering the curatorial logic that has governed the 'global art world'. I focus on the Kin ArtStudio as my main case study. I undertook research within this art space in 2016, from the 10th of April to the 15th of June, and again from the 16th of July to the 12th of September. My position as a participant observer turned out to be as engaging as informative. The Kin ArtStudio is a Kinshasa-based visual art platform founded in 2011 by the Congolese artist Vitshois Mwilambwe Bondo. It was established out of the will to empower emerging artists in that specific context, and facilitate the negotiation that the legitimization of their creations entails in today's global art and cultural dynamics. In order to evaluate the stakes of such negotiation, I start with reviewing the existing mechanisms, trends and networks that have legitimized visual art productions of the Democratic Republic of Congo on a global stage, as exemplified by the Beauté Congo "“ Congo Kitoko exhibition (2015). Then, my enquiry evolves towards specificity, towards the immediacy and the subjectivity that characterize Kinshasa's urban and socio-cultural context, and visual art practices therein. Subjectivity also applies to my four months immersive experience with that art space. Drawing from my observations, setbacks, hopes and recent academic and practical debates around contemporary art practices on the African continent, the role those art spaces can play in the curatorship, circulation, reception and commodification of contemporary art productions cannot be underestimated. While operating in lasting postcolonial settings, they are going through the negotiation of their global and translocal situatedness, which can in turn lead to new legitimizing narratives. These will more appropriately inform understandings of contemporary art practices of Africa, challenging the identifying prism sustained by the 'global art world'.
Keywords: Space (Art); Art -- Congo (Democratic Republic); Art and globalization; Postcolonialism and the arts -- Congo (Democratic Republic); Arts, Modern -- 21st century; Arts publicity; Arts, Modern -- 21st century -- Economic aspects; Arts, Modern -- 21st century -- Social aspects; Bondo, Vitshois Mwilambwe; Kin ArtStudio; Beauté Congo - 1926-2015 - Congo Kitoko